2022
DOI: 10.3390/healthcare10030568
|View full text |Cite
|
Sign up to set email alerts
|

Can Lung Ultrasound Be the Ideal Monitoring Tool to Predict the Clinical Outcome of Mechanically Ventilated COVID-19 Patients? An Observational Study

Abstract: Background: During the COVID-19 pandemic, lung ultrasound (LUS) has been widely used since it can be performed at the patient’s bedside, does not produce ionizing radiation, and is sufficiently accurate. The LUS score allows for quantifying lung involvement; however, its clinical prognostic role is still controversial. Methods: A retrospective observational study on 103 COVID-19 patients with respiratory failure that were assessed with an LUS score at intensive care unit (ICU) admission and discharge in a tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
3
11
0
2
Order By: Relevance
“…Similar COVID-19 pneumonia LUS findings have been already reported [ 13 , 33 ], but none described LUS specifically concerning CD, nor their evolution with treatment during the hospital stay. In our cohort, LUS findings prevalence improved along with successive time points, predominantly in CD− patients, consistent with other patients’ series [ 13 , 46 ]. In contrast, non-survivors showed an increase in the number of consolidations at D10.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar COVID-19 pneumonia LUS findings have been already reported [ 13 , 33 ], but none described LUS specifically concerning CD, nor their evolution with treatment during the hospital stay. In our cohort, LUS findings prevalence improved along with successive time points, predominantly in CD− patients, consistent with other patients’ series [ 13 , 46 ]. In contrast, non-survivors showed an increase in the number of consolidations at D10.…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that LUS scores obtained at D1 predicted the P/F ratio when using comprehensive cohort data. As reported in the literature, such findings were more pronounced in CD− patients during their hospital stay [ 42 , 46 ]. In CD+ patients, we found no correlation between LUS scores and the P/F ratio until D10.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Fifth , Vetrugno et al [ 21 ] found that semi-continuous assessment with LUS score associated with the clinical context could help to understand the patient trajectory, and described four phenotypes: Phenotype 1: patients with clinical improvement independent from the LUS evolution; Phenotype 2: patients who presented a moderate improvement in their ultrasound imaging; Phenotype 3: patients who responded very clearly, with a significant reduction in pulmonary involvement and LUS score; Phenotype 4: patients who, while improving their clinical conditions, did not show an evident improvement from an ultrasound point of view, or presented an apparent worsening in LUS. …”
mentioning
confidence: 99%